1999
DOI: 10.1034/j.1399-3003.1999.13b21.x
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors to bacterial colonization in chronic obstructive pulmonary disease

Abstract: The aim of this prospective observational study was to determine those factors influencing bacterial colonization in patients with stable chronic obstructive pulmonary disease (COPD).Eighty-eight outpatients with stable COPD and 20 patients with normal spirometry and chest radiography (controls) had a fibreoptic bronchoscopy performed with topical aerosol anaesthesia. Bacterial colonization was determined using the protected specimen brush (PSB) with a cut-off $10 3 colony-forming units (CFU . mL -1 ). The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
2
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(154 citation statements)
references
References 30 publications
7
139
2
6
Order By: Relevance
“…Similar rates were observed by Monso et al (25%), in 41 samples of patients with chronic bronchitis [14]. Previous studies have demonstrated both decreasing FEV1 and continued smoking as independent risk factors for lower respiratory bacterial colonization in advanced COPD [16].…”
Section: Discussionsupporting
confidence: 77%
“…Similar rates were observed by Monso et al (25%), in 41 samples of patients with chronic bronchitis [14]. Previous studies have demonstrated both decreasing FEV1 and continued smoking as independent risk factors for lower respiratory bacterial colonization in advanced COPD [16].…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have reported a persistent presence of PPMs in the LRT of individuals with chronic pulmonary disease, most prominently COPD (Cabello et al, 1997;Monsó et al, 1999;Zalacain et al, 1999). Likewise, microbiome analyses have revealed a change in microbial communities in the LRT including a reduction in microbiome diversity and an increased abundance of PPMs in subjects with COPD (ErbDownward et al, 2011;Garcia-Nuñez et al, 2014).…”
Section: Bacterial Pathogens Influencing the Response To Viral Infectionmentioning
confidence: 99%
“…influenzae is the most commonly found bacterial species in the lungs of COPD patients, being cultured from samples of about 25 % of all patients during stable disease (Cabello et al, 1997;Monsó et al, 1999;Zalacain et al, 1999). Exposure of respiratory epithelial cells to H. influenzae increases the expression of ICAM-1, the main receptor for major group HRV.…”
Section: Bacterial Pathogens Influencing the Response To Viral Infectionmentioning
confidence: 99%
“…Conversely, REs were significantly more frequent in smokers (420 packyear) or patients with pre-existing lung disease. There may be several explanations for the increased rate of REs in smokers: (i) cigarette smoke might impair the clearance and detoxification of bacteria, resulting in a higher prevalence of bacterial colonization of proximal or distal airways; 16,17 (ii) smoking is associated with immunologic disturbances; 18,19 (iii) in healthy long-term smokers, myocardial blood flow is impaired and the degree of impairment correlates with the number of years the patient has smoked; 20,21 and (iv) in animal models, cigarette smokes impairs cardiopulmonary function and increases capillary permeability. This could explain the hydration-related pulmonary edema occurring at the onset of chemotherapy.…”
Section: Respiratory Events In Acute Leukemia D Chaoui Et Almentioning
confidence: 99%